2017
DOI: 10.1371/journal.pone.0170083
|View full text |Cite|
|
Sign up to set email alerts
|

IGF-1 Induces GHRH Neuronal Axon Elongation during Early Postnatal Life in Mice

Abstract: Nutrition during the perinatal period programs body growth. Growth hormone (GH) secretion from the pituitary regulates body growth and is controlled by Growth Hormone Releasing Hormone (GHRH) neurons located in the arcuate nucleus of the hypothalamus. We observed that dietary restriction during the early postnatal period (i.e. lactation) in mice influences postnatal growth by permanently altering the development of the somatotropic axis in the pituitary gland. This alteration may be due to a lack of GHRH signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 43 publications
3
32
0
1
Order By: Relevance
“…Since GHRH neurons innervate the median eminence through a posteroventral loop highly difficult to follow by classical immunohistochemistry, we applied an in vitro approach by cultivating explants of arcuate nucleus. In agreement with our hypothesis, we observed that IGF-I significantly stimulates the axon growth of GHRH neurons in 24 hours in arcuate explants harvested from normally fed pups [17]. Interestingly, this effect seems preferential since no stimulations were observed for other populations of the arcuate nucleus studied all-at once (i.e.…”
Section: Text Bodysupporting
confidence: 91%
See 1 more Smart Citation
“…Since GHRH neurons innervate the median eminence through a posteroventral loop highly difficult to follow by classical immunohistochemistry, we applied an in vitro approach by cultivating explants of arcuate nucleus. In agreement with our hypothesis, we observed that IGF-I significantly stimulates the axon growth of GHRH neurons in 24 hours in arcuate explants harvested from normally fed pups [17]. Interestingly, this effect seems preferential since no stimulations were observed for other populations of the arcuate nucleus studied all-at once (i.e.…”
Section: Text Bodysupporting
confidence: 91%
“…The axon growth stimulating effect of IGF-I on GHRH neurons involves both the PI3K/AKT and, in a lower extent, the MERK/ERK signaling pathways as revealed by co-stimulations of IGF-I with LY294002 and PD0325901 specific inhibitors, respectively. However, when explants of arcuate nucleus were harvested from restricted pups, we observed that GHRH neurons lost their capacities to answer to IGF-I stimulation despite a controlled in vitro environment [17]. Western blot experiments on arcuate nucleus explants suggest that the absence of axon elongation observed for GHRH neurons in restricted pups is associated with impaired activation of the PI3K/AKT signaling pathway, whereas the activation capacity of the ERK/MEK pathway is maintained.…”
Section: Text Bodymentioning
confidence: 83%
“…It has been well-established that adverse developmental programming disrupts the normal wiring of the pathways that regulate energy balance via a disruption in neurite outgrowth in the ARC and changes in the expression of anorixigenic/orexigenic factors, including neuropeptide Y (NPY), proopiomelanocortin (POMC), and agouti-related peptide (AgRP). Similarly, it is well-known that the developmental settings of the somatotropic neuroendocrine axis are highly sensitive to alterations in early postnatal nutrition, suggesting that this subset of hypothalamic neurons (NPY, POMC, and AgRP) are particularly sensitive to changes in nutrition during the perinatal period [ 55 ]. However, the interactions between the factors regulating energy balance and GH-releasing hormone (GHRH) neurons in the ARC in the setting of early life programming remain poorly defined, and may reflect the “adaptive plasticity” of somatotropic functions allowing individuals to modify (i.e., decelerate) growth and conserve energy resources as per the PARS hypothesis, and thereby improving fitness in challenging postnatal environments [ 56 ].…”
Section: Animal Models Of Manipulation Of the Gh-igf Axismentioning
confidence: 99%
“…However, the interactions between the factors regulating energy balance and GH-releasing hormone (GHRH) neurons in the ARC in the setting of early life programming remain poorly defined, and may reflect the “adaptive plasticity” of somatotropic functions allowing individuals to modify (i.e., decelerate) growth and conserve energy resources as per the PARS hypothesis, and thereby improving fitness in challenging postnatal environments [ 56 ]. In cases of UN during lactation in the mouse, offspring show decreased circulating IGF-1 concentrations, which are associated with a reduced innervation of the median eminence by GHRH axons compared to control pups in the early neonatal period [ 55 ]. In vitro, IGF-1 stimulation preferentially stimulates axon elongation of GHRH neurons from normally nourished pups, whereas GHRH neurons derived from pups of UN mothers failed to respond to IGF-1 stimulation [ 55 ].…”
Section: Animal Models Of Manipulation Of the Gh-igf Axismentioning
confidence: 99%
See 1 more Smart Citation